Direito internacional dos refugiados na América Latina: o Plano de Ação do México e o Vaticínio de Hannah Arendt - Barichello, Stefania Eugenia Francesca Margherita (2009)
Latin America has been experiencing in the last years critical cases of forced displacement. This phenomenon is followed by the adoption of a series of initiatives that seem to follow successful efforts around the world. The approach of this thesis on International Refugee law in Latin America is justified on the Latin American tradition in terms of asylum, refugee and human rights, and intends to contribute by analysing the solidarity proposals of Mexico s Plan of Action based on the thought of Hannah Arendt. The general objective of this thesis is to investigate how the question of the International Refugee law in Latin America was configured, from the Cartagena Declaration on Refugees of 1984 until the Mexico Plan of Action of 2004, in order to contribute for the building of a a sui generis Latin American treatment regimen. The line of thought follows the reflection by Arendt on the basic requirements for the exercise of the human condition. Contemporary social, economic and political situations contribute to make men more superfluous and without a place in the world. The text is divided in two chapters. The first intends to provide an understanding of the asylum constitution and its consolidation under a juridical, social and individualist approach. The second chapter aims at understanding the International Refugee Law in Latin America, more specifically the Mexico Plan of Action, on the light of the intellectual legacy of Arendt. It pays particular attention to the meaning of citizenship as the right to have rights , fundamental to the human condition and collectively constructed in the public space. The final considerations point out to the advances of the proposals of the Mexico Plan s three programs in the search for more durable solutions and for the possibility for refugee and asylum seekers to have a life that goes beyond the biological life. What is more, a life that can reach political action and a full human condition, as prophesized Hannah Arendt.